Legal Counseling on Changing the Status of Building Use Rights to Ownership Rights in Merjosari Village, Lowokmaru District, Malang City - Sasmitaningtyas, Elmi; Pakage, Ferdinant; Kuswandono, Andi; Yuliadi, Prapto; Jauhari, Iman; Rafid, Rahmad; Supriadi; Tipagau, Nikolen (Universitas Kristen Cipta Wacana, 2024)
In 1997 the government regulated the policy of granting ownership rights to very simple houses and simple houses through KMNA/KBPN No. 9 of 1997 and KMNA/KBPN No. 6 of 1998 concerning Granting Ownership Rights to Residential Houses. The existence of this decision is very beneficial for land owners and residential houses located in housing complexes built by developers and for Indonesian citizens who own land with Building Use Rights for residential homes, it is easy to obtain changes to their land rights into Ownership Rights. To address the fact that in the statutory regulations, regulations regarding changing the status of Building Use Rights to Ownership Rights, it is deemed necessary to provide counseling/lectures so that the community in Merjosari Village, Lowokmaru District, Malang City knows the process and obstacles encountered in changing the status of Use Rights. The building becomes property rights. The counseling/lecture on the topic of changing the status of Building Use Rights to Ownership Rights involved lecturers from the Law Faculty of Cipta Wacana Christian University as a service team and involved law students from Cipta Wacana Christian University. Community service activities carried out in Merjosari Village, Lowokmaru District, Malang City can be said to have been carried out well in accordance with expectations.